Biological response to protein and energy supplementing in young bulls feeded with bean stubble (Phaseolus vulgaris L.) - Lozano Alva, Enrique (1978)
Tesis (M. Sc) -- CATIE; UCR, Turrialba (Costa Rica), 1978